Identification of Prognostic Genes in the Tumor Microenvironment of Hepatocellular Carcinoma - Xiang, Shixin; Li, Jing; Shen, Jing; Zhao, Yueshui; Wu, Xu; Li, Mingxing; Yang, Xiao; Kaboli, Parham Jabbarzadeh; Du, Fukuan; Zheng, Yuan; Wen, Qinglian; Cho, Chi Hin; et al. (Frontiers in Immunology, 2021)
Background: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors in the world. The efficacy of immunotherapy usually depends on the interaction of immunomodulation in the tumor microenvironment (TME). This study aimed to explore the potential stromal-immune score-based prognostic genes related to immunotherapy in HCC through bioinformatics analysis. Methods: ESTIMATE algorithm was applied to calculate the immune/stromal/Estimate score and tumor purity of HCC using TCGA transcriptome data. Functional enrichment analysis of differentially expressed genes (DEGs) was analyzed by DAVID. Univariate and multivariate Cox regression analysis and LASSO regression analysis were performed for prognostic gene screening. The expression and prognostic value of these gene were further verified by KM-plotter database and the Human Protein Atlas database. The correlation of selected genes with immune cell infiltration were analyzed by ssGSEA algorithm and TIMER. Results: Data analysis revealed that higher immune/stromal/Estimate score were significantly associated with better survival benefits in HCC within 7 years, while the tumor purity showed reverse trend. DEGs based on both immune and stromal scores primarily affected the cytokine-cytokine receptor interaction signaling pathway. Among the DEGs, there genes (CASKIN1, EMR3, GBP5) were found most significantly associated with survival. Moreover, the expression levels of CASKIN1, EMR3, GBP5 gene were significantly correlated with immune score/stromal score/Estimate score/tumor purity and multiple immune cell infiltration. Among them, GBP5 gene were highly related to immune infiltration. Conclusions: This study identified three key genes which were related to the tumor microenvironment and had prognostic significance in HCC, which may be promising markers for predicting immunotherapy outcomes.